2020
DOI: 10.3389/fpsyg.2020.545881
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and Somatization in Chronic Pain Patients: A Sequential Mediation Model

Abstract: To investigate whether chronic pain (CP) patients with somatization reported higher alexithymic traits than those without somatization and to study the different relationships between psychological characteristics, pain, health-related quality of life (HRQL), and somatization. Method: A consecutive sample of 134 CP treatment-seeking outpatients were evaluated for alexithymia (TAS-20), somatization (PHQ-15), distress (HADS), HRQL (SF-12), and pain (BPI). Results: Patients with somatization (37.04%) reported sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 85 publications
2
11
0
Order By: Relevance
“…Furthermore, depression mediated the relationship between alexithymia and several dimensions of illness perception in patients with systemic lupus erythematosus [ 32 ]. Moreover, the difficulty in identifying emotions affected somatization through distress and mental health impairment in patients with chronic pain, supporting the idea that alexithymia may increase somatic symptoms through emotional distress [ 33 ]. Finally, depression partially mediated the relationship between alexithymia scores and both physical and mental functioning in candidates for solid organ transplantation [ 24 ].…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, depression mediated the relationship between alexithymia and several dimensions of illness perception in patients with systemic lupus erythematosus [ 32 ]. Moreover, the difficulty in identifying emotions affected somatization through distress and mental health impairment in patients with chronic pain, supporting the idea that alexithymia may increase somatic symptoms through emotional distress [ 33 ]. Finally, depression partially mediated the relationship between alexithymia scores and both physical and mental functioning in candidates for solid organ transplantation [ 24 ].…”
Section: Introductionmentioning
confidence: 96%
“…Various, generally nonclinical, studies identified an association between alexithymia and different somatization measures (Kumar et al, 2018; Lanzara et al, 2020). A correlation between alexithymia and varying somatization measures has been found in numerous, often nonclinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The literature also reflects the possibility that individuals with early developmental trauma may process sensory input including psychological stress and pain, differently than others, due to a combination of factors that include sensory overload and somatic memory traces of abuse (42). An absence of feedback in the form of sensitive responsiveness and help with emotional regulation may similarly play an important role in validating painful emotional experiences within the attachment relationship (43)(44)(45). In one review of the literature, several familial risk factors for the development of somatoform disorders in youth were identified, including: somatization of parents, psychopathology of close family members, dysfunctional family climate, and traumatic experiences in childhood (46).…”
Section: Introductionmentioning
confidence: 99%